2017
DOI: 10.13031/aea.12333
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Capacity of Hog-Cooling Pad

Abstract: Abstract. Modern hog farrowing operations have reached a state in which the environmental conditions necessary for piglets are vastly different than those required by sows. A hog-cooling pad has been developed by Purdue University researchers to alleviate thermally-induced stress in the sow. Understanding the basic thermal properties of the device is critical to the development of the technology, and this article documents the experimentation performed on the unit to measure some of those characteristics. A pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In the above-mentioned study [ 77 ], air temperatures were within the range of 20.8 °C to 26.9 °C. However, the other scientists tested the effectiveness of conductive cooling in sows when the ambient temperature increased to a value of 35 °C [ 8 , 75 , 78 ]. It was found that conductive-cooling pads (water at 18 °C) was pumped through pads at a flow rate of 4 L/min affected lower respiratory rate during acute heat stress exposition [ 78 ].…”
Section: Cooling Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the above-mentioned study [ 77 ], air temperatures were within the range of 20.8 °C to 26.9 °C. However, the other scientists tested the effectiveness of conductive cooling in sows when the ambient temperature increased to a value of 35 °C [ 8 , 75 , 78 ]. It was found that conductive-cooling pads (water at 18 °C) was pumped through pads at a flow rate of 4 L/min affected lower respiratory rate during acute heat stress exposition [ 78 ].…”
Section: Cooling Technologiesmentioning
confidence: 99%
“…However, the increase of ambient temperature, which has been a global concern, calls for new methods and additional technology to improve cooling of the animals during summer. The heat stress conditions is a major factor which affect animal health and production, especially in modern genetic lines [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that sows within a farrowing room may be at different stages of lactation, have different litter sizes and be producing heat unequally, individual sow cooling has the possibility to confer more production and welfare benefits than whole room cooling. Recently, a cooling pad has been designed to increase the potential removal of excess heat of modern lactating sows in high environmental temperatures ( 31 ). It showed beneficial effects on the sows' respiration rates, and vaginal, skin, and rectal temperatures ( 32 ), with a “dose-dependent” decrease for all traits with increasing water flow rates from LOW to HIGH (from 0.25 to 0.85 L/min for 100 min) in comparison to a CONTROL flow rate (0.00 L/min).…”
Section: Introductionmentioning
confidence: 99%
“…The second group influences the immediate thermal vicinity of the animals. Examples for such AMs are floor cooling (conductive cooling) (Bull et al 1997;Cabezon et al 2017;Silva et al 2009), higher air velocity at the animal level to increase the convective heat release (wind-chill effect) (e.g., by tunnel ventilation, booster fans, and hybrid ventilation systems) (Zhang and Bjerg 2017), radiative cooling by a cooled cover of the laying zone (Pang et al 2010), cooled drinking water (Jeon et al 2006;Renaudeau et al 2012), wallows (Bracke 2011;de Mello et al 2017), or water baths (Huynh et al 2006). The AMs of the first group can be evaluated by simulation models at the housing level, whereas the second group needs models at the animal level, which describe the heat release and the thermal regulation for individual animals.…”
Section: Introductionmentioning
confidence: 99%